(untitled) (Global Journal of Management and Business Research, 2020)
Mobile banking is known as one of the latest as well as promising application of mobile commerce with great mobility and flexibility for the completion of financial transactions with the help of mobile communication devices. In today#x2019;s perspective, electronic banking, internet banking and mobile banking are considered as the buzzword as 4.5 billion mobile cellular subscriptions worldwide is estimated and mobile network has the capability to instantaneously offer mobile banking to 61% of total population. For both developed and developing countries the increase of adoption rate in Mobile banking shows the strong potential rate of growth.